Evaluation of the Glycosylated Haemoglobin as a Predictor of Severity of Coronary Artery Disease in Non-diabetic NSTEMI Patients (Cardiovascular Journal, 2022)
Background: Glycated hemoglobin (HbA1c) values reflect two to three months average endogenous exposure haemoglobin to glucose including postprandial spikes and have low intra-individual variability particularly in non-diabetic patients. Elevated HbA1c is regarded as an independent risk factor for coronary artery disease (CAD) in patients with or without diabetes mellitus (DM). The purpose of this study is to determine the correlation between the level of HbA1c and the severity of coronary artery disease in non-diabetic non ST elevation myocardial infarction (NSTEMI) patients.Methods: This observational study was carried out with total of 64 non-diabetic patients with a history of NSTEMI. Patients were divided into 2 groups based on HbA1c - one group having HbA1c ³5.7 – 6.4% (High risk group) and another group with HbA1c < 5.7% (Low risk group). Severity of CAD was assessed using Gensini score derived from coronary angiographic data. Gensini score < 36 points was regarded as mild coronary artery disease and Gensini score 36 points as moderate to severe coronary artery disease. Then patients with high and low risk HbA1C groups were correlated with severity of CAD.Results: Over 55.5% patients with HbA1c in high-risk group (5.7 – 6.4%) had severe CAD as opposed to 28.6% patients with HbA1c in low-Risk group (